المحاكمة عن بعد: سرعة الإجراءات أم إهدار للضمانات؟ - فليغة, خليل الله; لوحليط, يزيد (University of Eloued جامعة الوادي, 2021)
يعتبر استعمال التقنيات التكنولوجية الحديثة في قطاع العدالة خاصة تلك التي توفّر ميزة الاتصال المرئي والمسموع عن بعد من أهم مظاهر عصرنة قطاع العدالة، حيث يكتسي اعتماد هذه التقنية أهمية كبيرة في تكريس مبدأ سرعة الإجراءات، وضرورة البت في الدعوى في آجالا معقولة، وتخفيف الأعباء على كاهل القضاء والمتقاضين على حد سواء. تهدف هذه الدراسة إلى بحث مدى مشروعية نظام المحاكمة عن بعد، ومدى احترام ضمانات المحاكمة العادلة في ظل اعتماد هذا النظام لاسيما ما تعلقت بحقوق الدفاع، واحترام مبدأ المواجهة بين الخصوم، وتقييم فعاليته في مواجهة الظروف الطارئة التي قد تعيق السير العادي لإجراءات التقاضي. The use of modern technological technologies in the justice sector, especially those that provide the advantage of audio-visual communication from a distance, is one of the most important aspects of modernizing the justice sector, as the adoption of this technology is of great importance in establishing the principle of speedy procedures, and the necessity of deciding on the case in reasonable time, and reducing the burden on the shoulders both the judiciary and litigants. This study aims to examine the legality of the remote trial system, and the extent to which guarantees of a fair trial are respected in light of the adoption of this system, especially those related to the rights of defense, respect for the principle of confrontation between litigants, and an evaluation of its effectiveness in the face of emergency circumstances that may hinder the normal course of litigation procedures.
مجلد12، عدد1
Keywords: المحاكمة عن بعد ; سرعة الإجراءات ; ضمانات المحاكمة العادلة ; عصرنة العدالة ; حق الدفاع; Distance trial; speed of procedures; fair trial guarantees; modernization of justice; right of defense.